Exploring the effectiveness of STEM education on the creativity of 5-year-old kindergarten children - Uret, Aytul; Ceylan, Remziye (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
In this study, the effect of STEM education on the creativity of 5-year-old children was examined. This article presents the relationship between STEM education and creativity in early years of childhood. The semi-experimental method with pretest-posttest-control group is used to observe the difference of creativity scores between study group and control group. 'Torrance Tests of Creative Thinking Figural A Form and Figural B Form' were used as data collection tools in the research. As a result of the research, a statistically significant difference was found between the experimental and control group Torrance Tests of Creative Thinking pretest/ posttest total scores (p < .05). The results revealed that the effect of STEM education on the creativity of 5-year-old children attending kindergarten is positive and this effect is permanent.
Keywords: early childhood education; STEM education; creativity; preschool education; early years; science education; kindergarten; Education & Educational Research